1987
DOI: 10.1029/jc092ic07p06805
|View full text |Cite
|
Sign up to set email alerts
|

Variations of mesoscale and large‐scale sea ice morphology in the 1984 Marginal Ice Zone Experiment as observed by microwave remote sensing

Abstract: During the summer 1984 Marginal Ice Zone Experiment in the Fram Strait and Greenland Sea (MIZEX '84), passive and active microwave sensors on five aircraft and the Nimbus 7 scanning multichannel microwave radiometer (SMMR) acquired synoptic sequential observations which when combined give a comprehensive sequential description of the mesoscale and large-scale ice morphology variations during the period June 9 through July 16, 1984. The high-resolution ice concentration distributions in these images agree well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We assigned sea-ice concentrations of 40%–50% to be indicative of the average paleo-sea-ice edge, because these values are in the middle of the abrupt decline of Antarctic sea-ice concentration, which marks the modern sea-ice edge 35 36 . A similar definition of the average sea-ice edge was proposed based on microwave remote-sensing observations 37 . Our sediments document the last glacial, the glacial–interglacial transition and the early part of the Holocene ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We assigned sea-ice concentrations of 40%–50% to be indicative of the average paleo-sea-ice edge, because these values are in the middle of the abrupt decline of Antarctic sea-ice concentration, which marks the modern sea-ice edge 35 36 . A similar definition of the average sea-ice edge was proposed based on microwave remote-sensing observations 37 . Our sediments document the last glacial, the glacial–interglacial transition and the early part of the Holocene ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…These eddies in Fram Strait have been described (Wadhams and Squire, 1983;Manley, 1987) from observations taken by ship (1. , by remotely sensed properties (Shuchman et al. 1985;Campbell et al, 1987), and by moored current meters (Muench et al, 1986;Manley et al, 1987). In an earlier study, we suggested that these eddies had an important role in the biological events of the marginal ice zone because they could cause the uplift of nitrate-rich water into a euphotic zone stabilized by melting ice (Smith et al, 1985).…”
Section: Introductionmentioning
confidence: 92%
“…Significant physical processes in MIZ include momentum exchange across the air-ice boundary (MIZEX'84: Campbell et al, 1987;Claussen, 1991;Perrie and Hu, 1996;Birnbaum and Lupkes, 2002;Ivanov et al, 2003;Fer and Sundfjord, 2007), wave dynamics in the MIZ (Wadhams et al, 1988;Squire et al, 1995), heat (Perovich et al, 1989) and salt fluxes (McPhee et al, 2008), turbulence over MIZ (Drue and Heinemann, 2002), and floe size distribution (Lu et al, 2008). These processes have various feedbacks, each of which being directly or indirectly linked with the roughness of the MIZ.…”
Section: Introductionmentioning
confidence: 99%